2010
DOI: 10.1002/dvdy.22331
|View full text |Cite
|
Sign up to set email alerts
|

Three consecutive generations of nephridia occur during development of Platynereis dumerilii (Annelida, Polychaeta)

Abstract: *Molecular data for nephridial development in polychaetes are not available yet. The scope of our work was to establish a reference system for future investigations using two markers for nephridial development: b-tubulin as marker for cilia and alkaline phosphatase (AP) activity for secretory epithelia. The markers identified, unexpectedly, three consecutively forming generations of nephridia: (1) a transitory unciliated, but AP-positive head kidney, (2) a transitory larval nephridium, which undergoes a morpho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 29 publications
1
10
0
Order By: Relevance
“…The larval nephridium (also called ciliated protonephridia (Hasse et al, 2010)) is found adjacent to the longitudinal muscles, located laterally between the 2nd and 3rd larval segments (Figure 1E, Figure 2D, Supplementary Figure 1B). It is composed of 7 cells on each side of the body which connect to the coelomic cavity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The larval nephridium (also called ciliated protonephridia (Hasse et al, 2010)) is found adjacent to the longitudinal muscles, located laterally between the 2nd and 3rd larval segments (Figure 1E, Figure 2D, Supplementary Figure 1B). It is composed of 7 cells on each side of the body which connect to the coelomic cavity.…”
Section: Resultsmentioning
confidence: 99%
“…To evaluate the quality of cellular segmentation, we focused on the larval nephridia ( Figure 2D). Previous transmission EM analysis had shown that the larval nephridia are embedded between the body surface muscles and oblique muscles, and that the tubule wall is formed from single cells wrapping around a tight lumen with six cilia constantly present (Hasse et al, 2010). However, transmission EM on single sections could not resolve how many cells contribute to this structure and how many distinct cilia they protrude into the lumen.…”
Section: Segmentation Of Nuclei Cells Tissues and Body Partsmentioning
confidence: 97%
“…Invertebrate alkaline phosphatases appear to have a similar association with transport: ALP activity has been reported in excretory organs of insects and annelids, salivary glands of insect larvae, and the guts of diverse species (Myohara, 2004;Eguchi, 1995;Hasse et al, 2010;Kitamura and Shimizu, 2000).…”
Section: Introductionmentioning
confidence: 85%
“…In other annelids, alkaline phosphatases display fairly restricted activity both in space and in developmental time. Although Kitamura and Shimizu (2000) and Hasse et al, (2010) are studies of embryos and juveniles, Myohara's (2004) observations on adult E. japonensis worms suggest that widespread ALP activity in mesodermal tissues is, at the very least, not a universal feature of annelids. Interestingly, alkaline phosphatase activity in muscle tissue of a euryhaline crustacean appears to respond to changes in environmental salinity (Pinoni et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, both types do occur subsequently during ontogeny in certain polychaetes (e.g. [42]). The finding of a cilium in a podocyte of Lepidochitona corrugata – remarkably the first report of a podocyte bearing a cilium in a mollusc – lends substantial support to this concept.…”
Section: Discussionmentioning
confidence: 99%